Ambulatory intravenous ceftriaxone in paediatric A&E: a useful alternative to hospital admission?. Issue 10 (15th February 2011) - Smith, Jennifer K; Alexander, Saji; Abrahamson, Ed
Abstract : Background: Treatment of children with intravenous ceftriaxone on an ambulatory basis is described. This allows a child to remain at home, but also be reviewed regularly when attending the Emergency Department for antibiotics. Methods: Indications for, and length of, treatment and laboratory parameters were recorded. Also, a survey of children's parents was undertaken to ascertain opinions regarding ambulatory treatment. Results: 36 patients were treated with ambulatory ceftriaxone over 4 months. Indications included fever without focus, tonsillitis, periorbital cellulitis, urinary tract infection, petechial rash and lymphadenitis. Median duration of treatment was 2.3 days. There was no occult bacteraemia but five positive urine cultures. There was one failure of treatment with subsequent admission for alternative intravenous antibiotics. Conclusions: Parental opinion favours ambulatory treatment, with 94% of parents acknowledging they would choose it again in similar circumstances. Cost analysis favours ambulatory treatment based on predicted costs of a similar length of inpatient stay.